Effects of the chymase inhibitor fulacimstat in diabetic kidney disease—results from the CADA DIA trial. Issue 12 (26th December 2020) - Rossing, Peter; Strand, Jorma; Avogaro, Angelo; Becka, Michael; Kanefendt, Friederike; Otto, Christiane
Abstract: Background: The protease chymase generates multiple factors involved in tissue remodelling including angiotensin II (Ang II) and has been implicated in the pathophysiology of diabetic kidney disease (DKD). This study investigated the effects of the chymase inhibitor fulacimstat on albuminuria in patients with Type II diabetes mellitus and a clinical diagnosis of DKD. Methods: In this double-blind, randomized, placebo-controlled trial, patients were on the maximum tolerated dose of either an Ang II receptor blocker or an Ang-converting enzyme inhibitor since at least 3 months before the screening visit. Eligible patients were randomized in a 2:1 ratio to treatment with either 25 mg fulacimstat ( n  = 99) or placebo ( n  = 48) twice daily on top of standard of care. Results: The randomized patients had a mean urine albumin–creatinine ratio (UACR) of 131 mg/g (range: 29–2429 mg) and a mean (standard deviation) estimated glomerular filtration rate of 60.8 ± 16.9 mL/min/1.73 m 2 before treatment start. Fulacimstat was safe and well tolerated, and achieved mean total trough concentrations that were ∼9-fold higher than those predicted to be required for minimal therapeutic activity. UACR increased by 27.4% [coefficient of variation (CV) 86%] and 3% (CV 88.9%) after 24 weeks of treatment with placebo or fulacimstat, respectively. Analysis of covariance revealed a least square mean UACR ratio (fulacimstat/placebo) of 0.804 (90% CI 0.627–1.030, P = 0.1477), indicating a statistically non-significant UACR reduction of 19.6% after fulacimstat treatment compared with placebo. Conclusions: Fulacimstat was safe and well tolerated but did not reduce albuminuria in patients with DKD. These findings do not support a therapeutic role for chymase inhibition in DKD.